PENGARUH KEPEMILIKAN MANAJERIAL, KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, DAN KEBIJAKAN DIVIDEN PADA NILAI PERUSAHAAN DI BURSA EFEK INDONESIA - Ferry Ananta, Gede Eka; Sadha Suardikha, I Made; Dwi Ratnadi, Ni Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 03.NO.09.TAHUN 2014, 2014)
1024x768 A firm value is a particular condition which has been achieved by a company as an overview of society belief of firm that has through a process of activities for several years, namely since the company was established until the present. This research aims to examine the effect of managerial ownership, investment decisions, financing decisions, and dividend policy on the firm value in Indonesia Stock Exchange from 2009 until 2012. The selecting sample method is using purposive sampling thus obtained 35 firms of the sample total number within 128 observations. This data is analyzed by using a multiple linear regression analysis. Meanwhile the regression model has been examined by a classical assumption of regression analysis. In conclusion the analysis result showed that the investment decision and financing decision affect the firm value however, managerial ownership and dividend policy do not affect the firm value . Keywords : Managerial Ownership, Investment Decisions, Financing Decisions, Dividend Policy, and Firm Value Normal 0 false false false EN-US X-NONE X-NONE 1024x768 A firm value is a particular condition which has been achieved by a company as an overview of society belief of firm that has through a process of activities for several years, namely since the company was established until the present. This research aims to examine the effect of managerial ownership, investment decisions, financing decisions, and dividend policy on the firm value in Indonesia Stock Exchange from 2009 until 2012. The selecting sample method is using purposive sampling thus obtained 35 firms of the sample total number within 128 observations. This data is analyzed by using a multiple linear regression analysis. Meanwhile the regression model has been examined by a classical assumption of regression analysis. In conclusion the analysis result showed that the investment decision and financing decision affect the firm value however, managerial ownership and dividend policy do not affect the firm value . Keywords : Managerial Ownership, Investment Decisions, Financing Decisions, Dividend Policy, and Firm Value 1024x768 A firm value is a particular condition which has been achieved by a company as an overview of society belief of firm that has through a process of activities for several years, namely since the company was established until the present. This research aims to examine the effect of managerial ownership, investment decisions, financing decisions, and dividend policy on the firm value in Indonesia Stock Exchange from 2009 until 2012. The selecting sample method is using purposive sampling thus obtained 35 firms of the sample total number within 128 observations. This data is analyzed by using a multiple linear regression analysis. Meanwhile the regression model has been examined by a classical assumption of regression analysis. In conclusion the analysis result showed that the investment decision and financing decision affect the firm value however, managerial ownership and dividend policy do not affect the firm value . Keywords : Managerial Ownership, Investment Decisions, Financing Decisions, Dividend Policy, and Firm Value Normal 0 false false false EN-US X-NONE X-NONE Normal 0 false false false EN-US X-NONE X-NONE
Keywords: Managerial Ownership, Investment Decisions, Financing Decisions, Dividend Policy, and Firm Value